Thick Film Resistors on Dielectrics as Temperature Detectors - Benedykt Rzasa; Jerzy Potencki (Active and Passive Electronic Components, 1986)
Thick film resistors made of typical ruthenate pastes on various dielectrics change their properties. The properties of such resistors, fabricated on the TiO2 + glass dielectric, have been evaluated in this paper. The usability of the structures of the type conductor-dielectric-resistor for the construction of temperature sensors has been determined. A practical solution for the temperature sensor, in the form of an RC network with distributed parameters, together with a circuit for the conversion of temperature into frequency has been presented.